Democracy versus the rule of law in conditions of disturbed political balance - Zaleśny, Jacek (Scientific Journal of Bielsko-Biala School of Finance and Law, 2022)
The article advances the hypothesis that republican relations are losing their importance in contemporary states in favour of democratic ones, which are at the same time a façade for globally implemented oligarchic relations. Crises concerning the rule of law and democraticality are taking place in the vast majority of states which until recently were considered to be law-abiding and democratic. To test this hypothesis, the paper uses the comparative method. The processes occurring in the contemporary world provide the background for an analysis of the conflicts taking place in Poland between democraticality and the rule of law. It is shown that a reduction in the rule of law is connected with a return to a socialist understanding of power in which politics prevails over the law.